ChemInform Abstract: Synthesis and Characterization of the Divalent Samarium Zintl‐Phases SmMg2Bi2 and SmMg2Sb2. Issue 51 (December 2015) - Ramirez, D.; Gallagher, A.; Baumbach, R.; Siegrist, T.
Abstract: Single crystals of LnMg2 Bi2 (Ln: Yb, Eu, Sm) and SmMg2 Sb2 are prepared from elemental Ln in a reactive Mg/Bi or Mg/Sb flux (molar ratio of Mg:Bi(Sb):Ln = 25:5:1, 1000 °C, 20 h).